TIMELINES OF EXTRAORDINARY LIVES : From Cleopatra and Confucius to Mozart and Malala (London : Dorling Kindersley Limited, 2024)
"More than 150 visual timelines take children aged 9-12 on unforgettable journeys through the lives of the great, the terrible, and the overlooked people of world history. SI Timelines of Extraordinary Lives focuses on the incredible biographies of a myriad of movers and shakers across millennia. Children will be fascinated by the lives of a diverse array of kings and queens, humanitarians, scientists, inventors, explorers, activists, writers, artists, and more, from across the globe"--
Includes index
Keywords: Celebrities -- Biography; World history; Chronology, Historical; Men -- Biography; Women -- Biography; Biographies